The populist style and public diplomacy: kayfabe as performative agonism in Trump's Twitter posts. (January 2021) - Surowiec, Paweł; Miles, Christopher
This article theorises the interplay between public diplomacy and populism. Building on Baudrillard's simulacra, we advance the hybridity approach to soft power statecraft by analysing a cultural shift in US presidential public diplomacy. Using discourse analysis, we uncover how, rather than aiding the building of relationship with foreign publics, Donald Trump has brought to the field cultural codes alien to public diplomacy, imploding the meanings central to the endogenous norms of diplomacy and turning towards an agonistic relational dynamic with foreign publics. This article reveals how digitalisation affords the expansion of Donald Trump's populist style, and makes the populist cultural shift highly visible on his Twitter. To reveal this dynamic in granular detail, we propose 'kayfabe' as an epistemic lens for the interpretation of the populist style in the conduct of Trump's 'simulated public diplomacy', a defining feature of the current US global leadership. As well as considering socialities re-shaping relational dynamics, this article unpacks tensions stemming from the expansion of populist style into presidential public diplomacy. Finally, we reflect on the epistemic crisis of US public diplomacy within the strategic landscape of political uncertainties associated with the proliferation of populism in the field.